2019
DOI: 10.1007/s00402-019-03142-6
|View full text |Cite
|
Sign up to set email alerts
|

Cement augmentation of the proximal humerus internal locking system in elderly patients: a multicenter randomized controlled trial

Abstract: Introduction Cement augmentation of the proximal humerus internal locking system (PHILOS) screws might reduce complication rates in osteoporotic bones. This study compared the risk of mechanical failure during the first year after PHILOS™ treatment of proximal humerus fractures (PHF) without (control group) and with (augmented group) screw augmentation. Secondary objectives were to report shoulder functions, quality of life (QoL), adverse events (AEs), and reoperation rates. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 49 publications
2
30
1
1
Order By: Relevance
“…The total revision rate using screw-tip augmentation in this study accounted for 16.7% and is located in the lower range of comparable, previously published data of conventional angular stable plating in PHFs, which showed revision rates from 13% up to 28% in an elderly population [ 2 , 4 , 7 , 16 , 18 ].…”
Section: Discussionsupporting
confidence: 66%
“…The total revision rate using screw-tip augmentation in this study accounted for 16.7% and is located in the lower range of comparable, previously published data of conventional angular stable plating in PHFs, which showed revision rates from 13% up to 28% in an elderly population [ 2 , 4 , 7 , 16 , 18 ].…”
Section: Discussionsupporting
confidence: 66%
“…In the clinical setting, PMMA has been used to improve screw fixation in osteoporotic bone such as wrist and proximal femur fractures, in order to fill subchondral voids in tibial plateau fractures and provide structural support in metaphyseal fractures or vertebral fractures [ 4 , 47 , 48 ]. Three studies reported the results of polymethyl-methacrylate (PMMA) injectable cement for PHF augmentation [ 30 , 31 , 32 , 33 , 34 ], for a total of 96 patients with a mean age of 75.86 years (range of 64–92), with the purpose of reinforcing the screw-bone interface after plating fixation. In all the three studies, the same PMMA (Trauma Cem V; DePuySynthes, West Chester, PA, USA) was used.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Hengg et al [ 34 ], in a multicenter randomized controlled trial, enrolled 67 patients older than 65 years with displaced or unstable PHF. They compared the risk of mechanical failure during the first year after PHILOS plating without (control group, 34 patients) and with (augmented group, 33 patients) screw augmentation with PMMA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While we did not include row C in our analysis, this screw row of the PHILOS plate is not recommended by the surgical guide as, firstly, the tips often lie at the same level as row A, and secondly because row C screw tips often end close to fracture lines. Hengg et al 14 performed the only multicentre randomized prospective trial to date on the use of cement augmentation. However, their study was abandoned when early analysis showed the design to be underpowered based on an overestimation of failure rates seen with fixation.…”
Section: Discussionmentioning
confidence: 99%